Modeling and Characteristic Test for a Crank-Connecting Rod Mem-Inerter Device - Xiao-Liang Zhang; Ya-Lin Chen; Jia-Mei Nie; Wei-An Zhu (Machines)
This paper presents a mechanical crank-connecting rod mem-inerter device, with its output and memory characteristics being investigated and validated. Previous research suggests that a hydraulic mem-inerter generates a sizeable damping force, practically transforming it into a mem-dashpot. This greatly influences a system’s vibration characteristics when using a hydraulic mem-inerter. In contrast, the proposed crank-connecting rod inerter exhibits negligible damping force, addressing the issue of excessive damping in hydraulic inerters and potentially enhancing the actual isolation effect. We successfully developed a prototype of the trial production device, and a bench characteristic test was conducted. Our quasi-static test results indicate that frictional resistance during device operation can be negligible. Our dynamic characteristic test results reveal that the characteristic curves of the device on the momentum–velocity plane can be displayed as a pinched hysteresis loop. Our results are in agreement with the simulation outcomes, which proves that the crank-connecting rod inerter is a physical realization of a mem-inerter device.